2D vanadium doped manganese dioxides nanosheets for pseudocapacitive energy storage. Issue 38 (15th September 2015) - Hu, Zhimi; Xiao, Xu; Huang, Liang; Chen, Chi; Li, Tianqi; Su, Tiecheng; Cheng, Xiaofeng; Miao, Ling; Zhang, Yanrong; Zhou, Jun
Abstract : This work demonstrates the successful growth of 2D V-doped MnO2 nanosheets by facile hydrothermal process, which offers great potential for energy storage. Abstract : Ultrathin two-dimensional (2D) crystals have been predicted to have high electrochemical activity because nearly all active atoms are exposed to the electrolytes, which offers great potential for energy storage. However, to construct layered structure metal oxides, simplifying the synthetic methods and improving the electronic conductivity remain a challenge. Herein, we synthesized 2D vanadium doped manganese oxides through a facile hydrothermal method. Vanadium dopant is also used as a template agent for the formation of nanosheet-shaped MnO2, further leading to high specific surface area as well as significant enhancement of the electronic conductivity, as confirmed by the first-principle calculations and four-point probe method. For the sake of a shortened ion transport distance and enhanced electronic conductivity, V-doped MnO2 nanosheets display an excellent electrochemical performance as a supercapacitor electrode.